Defective CFTR promotes intestinal proliferation via inhibition of the hedgehog pathway during cystic fibrosis. (1st April 2019) - Liu, Kaisheng; Wang, Xiao; Zou, Chang; Zhang, Jieting; Chen, Hao; Tsang, Lailing; Yu, Mei Kuen; Chung, Yiu Wa; Wang, Jianhong; Dai, Yong; Liu, Yang; Zhang, Xiaohu
Abstract: Hyperproliferation occurs in a variety of tissues and organs during cystic fibrosis (CF). However, the associated molecular mechanisms remain elusive. We investigated the molecular link between cystic fibrosis transmembrane conductance regulator (CFTR) defects and hyperproliferation, and showed that the length of the entire gastrointestinal tract was longer and the intestinal crypts were deeper in CF mice compared to those in wild-type animals. PCNA expression increased in CF mouse intestines and CFTR-knockdown cells. Villin1, an intestinal differentiation marker, was downregulated in CF mice. Ihh and Gli1 were significantly downregulated, whereas TCF4 was activated in CF mouse intestines and CFTR-knockdown Caco2 cells. Importantly, β-catenin activators rescued Gli1 suppression, suggesting that hedgehog signaling might be mediated by the Wnt/β-catenin pathway in the absence of functional CFTR. Moreover, PCNA positivity in the crypts of CF mice was alleviated by LiCl, which activates Wnt/β-catenin signaling. Further, a strong positive correlation was observed between the expression of CFTR and Ihh in intestines. Our study revealed a previously unidentified role of CFTR in regulating hedgehog signaling through β-catenin, providing novel insights into the physiological function of CFTR and CF-related diseases. Highlights: Gastrointestinal tract length, crypt depth, and proliferation are increased with CFTR ablation. Ihh, Gli1, and differentiation are downregulated in CF mice and TCF4 is activated. Hedgehog signaling might be mediated by Wnt/β-catenin in the absence of CFTR. This study suggests a role for CFTR in regulating hedgehog through β-catenin.